OPTIMIZATION OF SCHOOL CHAIR DESIGN USING FINITE ELEMENT METHOD ANALYSIS - Spiroski, Zoran; Koljozov, Vladimir; Trposki, Zoran; Temelkova, Anastasija (FDTME-Skopje, 2025)
The aim of the research presented in this paper was to study the possibilities of using the SOLIDWORKS Simulation software application to determine the optimal values of the structural and strength characteristics in the design process of a school chair. By using an optimization analysis module, a simulation of the real loads on a school chair was carried out. Through several iterations with virtual prototypes, the optimal values for the dimensions of the elements were determined from the aspect of durability of static loads
Keywords: finite element method, Optimization analysis, SOLIDWORKS Simulation, Virtual prototypes